Using literary texts to develop grammatical and lexical competence in brazilian university students - Mouta, Antonio Lopes (1999)
This dissertation outlines a scheme for teaching literature which is based on an approach to teaching literature which emerged in England in the early 1980s. The scheme was designed to meet the essential needs of Brazilian university students who attend the course in Letters at Faculdade de Educação, Ciências e Letras de Iguatu (Faculty of Education, Sciences and Letters of Iguatu), in Brazil. The main feature of this approach is to use literature for language learning purposes. As these students are weak in grammar and lexis, twelve literary texts were chosen and a set of activities were devised in order to improve their grammatical and lexical competence. The importance of such an approach lies in making use of linguistic areas such as psycholinguistics, sociolinguistics, semantics, stylistics, morphology, syntax, functionalism, and others in literature teaching. That is the reason why it is called 'language-based approach to teaching literature.' An attempt was made to review the role of literary texts in language teaching over the years. It was observed that they played an important role when the grammar-translation method was in progress. Then they were relegated to a peripheral role, and only in the early 1980s did they receive special attention from applied linguists and theorists. Close attention was given to the theoretical and practical aspects of the approach in question in comparison with those of the content- based one. The former is centred on the student and the process and aims at developing linguistic competence while the latter is centred on the teacher and the product, and its major goal is to develop literary competence. The work weighs up the advantages and disadvantages of both approaches and regards the language-based approach to teaching literature as the best way to teach literature in the university institution mentioned above. As far as I could conclude, such an approach may provide those students with a good basis of grammatical and lexical knowledge which may help them to develop their reading comprehension of literary texts.